New view on Taekwondo athletes` chronic weight control before competition - Yan, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The national Taekwondo championships during April 2007 were conducted under the amended rules for the first time. Rule changes increased the intensity of the competition. A challenge for Taekwondo athletes is to adapt to high intensity competition while maintaining adequate functional condition and stability after weight-loss, a small group of nine elite Taekwondo athletes were studied. Methods Athletes` weight and body composition were measured and individual weight-reduction goals were established for different athletes. The implementation period was 35 days, which occurred from 40 days to 5 days before the competition. According to the weight-loss goals, on the basis of chronic weight control, the Taekwondo athletes continuously lost weight every week by prolonging the active relaxation time after daily specific training. Furthermore, blood tests were conducted every two weeks to monitor the athetes` functional condition through physiological and biochemical indices (in the 1st, 3rd and 5th weeks, for a total of 3 times). These indices included Hb, Hct, red cell, BUN, CK, T, C and T/C. Results For female athletes, the results indicated no significant amount of weight loss (P<0.078), but body fat had been reduced (P<0.009), and lean body mass had increased (P<0.657). For male athletes, the results showed body weight had changed after weight-loss (P=0.004), body fat had been reduced (P=0.043) and lean body mass had been reduced (P=0.020). Most of the physiological and biochemical indices showed changes. Conclusions It can be concluded that the athletes` body weight and body fat had both reduced, and changes in lean body mass were evident. The athletes` functional condition remained stable and the athletes` relative athletic abilities had been improved. The results of the study are more beneficial for female rather than male athletes, and can be expressed by the new theory of "small machine but strong power".